2021
DOI: 10.3390/ijerph182010978
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety in Dental Students during the COVID-19 Outbreak: A Meta-Analysis

Abstract: Background: Since the onset of the COVID-19 pandemic, the psychological state of university students has been a cause for concern. In particular, odontology students have experienced symptoms of anxiety due to the closure of universities and the suspension of clinical training. Methods: Medline via PubMed was searched for studies on the prevalence of anxiety in dental undergraduates, published from 1 December 2019 to 1 August 2021. Results: A total of fifteen studies were included in this review. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 89 publications
3
25
2
2
Order By: Relevance
“…Studies prior to the pandemic reported that university students suffer from higher levels of depression and anxiety than the general population. Moreover, levels of depression and anxiety have been higher among dental students than among university students in general, particularly since the beginning of the pandemic [56,57]. In addition to the higher scores for depression and anxiety among bruxers in the present study, the multiple logistic regression model did not reveal a significant association.…”
Section: Discussioncontrasting
confidence: 78%
“…Studies prior to the pandemic reported that university students suffer from higher levels of depression and anxiety than the general population. Moreover, levels of depression and anxiety have been higher among dental students than among university students in general, particularly since the beginning of the pandemic [56,57]. In addition to the higher scores for depression and anxiety among bruxers in the present study, the multiple logistic regression model did not reveal a significant association.…”
Section: Discussioncontrasting
confidence: 78%
“…Firstly, as previously stated, we have found that the levels of PTSD among university students are some of the highest found within the groups analysed [56,59,81]. They are also close to the levels of other symptomatologies, such as stress, depression or anxiety [4,27,72,82]. Therefore, this research confirms that we are facing a very important mental health problem among young people.…”
Section: Discussionsupporting
confidence: 86%
“…This is addressed by the 2030 Agenda, which states that quality education (SDG4) must be achieved among university students, and for which it is essential that they enjoy physical and mental health and wellbeing (SDG3). Taking care of university students' mental health can also prevent psychological problems developing in later adulthood and during professional life [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another systematic review, Santabarbara et al ( 32 ) assessed the prevalence of anxiety among dental students during the outbreak of COVID-19. In their sample of 15 studies, anxiety had been reported by 35% of dental students, independent of gender, response rate, and methodological quality.…”
Section: Discussionmentioning
confidence: 99%